Elektromobilität und Ladesäulenstandortbestimmung: Eine exemplarische Analyse mit dem Beispiel der Stadt Duisburg - Sascha Bioly; Viktor Kuchshaus; Matthias Klumpp (MA Akademie Verlags- und Druck-Gesellschaft mbH, 2012)
– In the context of future e-mobility concepts one important research question is the location for public loading stations. Nowadays a study for Berlin has analyzed a location distribution for a e-mobility structure based on existing electricity infrastructure. In contrast to that this paper will analyze the end customer perspective regarding possible loading station spots in e-mobility concepts in the city of Duisburg, North Rhine-Westphalia. The paper at hand describes and compares two different methods of research. On the one hand a consumer survey and on the other hand an analysis of existing data of liable parking areas in Duisburg. Based on this analyzed data a classification of the consumer's behavior will be enabled. This classification can be grouped in 3 categories: short-term, mid-term and long-term parking. These three categories can determinate which locations and which kind of loading station are requested by the today's consumers parking behavior and by the survey results of the interviewed consumers.
Keywords: 650; Motorisierter Individualverkehr; Elektrofahrzeug; Verkehrsinfrastruktur; Energieversorgung; Batterie; Nachhaltige Mobilität; Deutschland; Duisburg